2022
DOI: 10.1108/jhti-05-2022-0164
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the terrorism–tourism nexus in Nigeria: the moderating role of military spending

Abstract: PurposeTourism development is critical for economic transformation, particularly in emerging economies. However, the growing spate of terrorism dissuades international tourists, reduces tourism receipts and ultimately hampers the tourism sector's performance. Thus, the government intervenes by altering its military spending to curtail terrorism. Against this backdrop, this study examines the moderating role of military spending in the terrorism–tourism nexus in Nigeria.Design/methodology/approachThe study empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Previous studies have also shown that institutional quality is crucial for stimulating investment (Abotsi, 2018; Letete & Sarr, 2017), hence, its inclusion in the model. In line with Raifu et al (2022), the principal component analysis (PCA) was used to compute the institutional quality index using the six institutional indicators (bureaucratic quality, control of corruption, democratic accountability, government stability, regulatory quality and rule of law). The index is normalized to range from 0 to 1.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have also shown that institutional quality is crucial for stimulating investment (Abotsi, 2018; Letete & Sarr, 2017), hence, its inclusion in the model. In line with Raifu et al (2022), the principal component analysis (PCA) was used to compute the institutional quality index using the six institutional indicators (bureaucratic quality, control of corruption, democratic accountability, government stability, regulatory quality and rule of law). The index is normalized to range from 0 to 1.…”
Section: Methodsmentioning
confidence: 99%
“…This is because financial resources are as important as physical and human resources for increased productivity and they are essential for acquiring the requisite modern resources (human and physical capital as well as technology) needed to power economic transformation (Signé et al , 2020; Muslim et al , 2021). However, leakages from the economy pose severe threats to the achievement of development agendas and economic transformation (Oji and Afolabi, 2022; Raifu et al , 2022). This partly explains the pervasive poverty, rising unemployment and widening income gaps in Nigeria despite being the giant of Africa, in terms of gross domestic product and population.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there could be a case of reverse causality between military spending and health expenditure because it is possible that a high level of military expenditure can displace health expenditure due to the issue of budget constraints. In the same vein, it is possible that theb poor health conditions prevailing in a country can necessitate an increase in military spending to social stability by ensuring the security of lives and property (Raifu and Aminu, 2023;Afolabi, 2023a, b;Raifu, Afolabi and Oguntimehin Jr, 2022). Generally, estimating GMM involves two main steps.…”
Section: Methodsmentioning
confidence: 99%